Pengaruh Keselamatan dan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan: Narrative Literature Review - novitasari, dewiana; Suwandy, Safna Deviputri; Asbari, Masduki; Rahman, Yuniar (Jurnal Bisnis Manajemen dan Akuntansi, 2023)
Abstract - Based on data from the Central Statistics Agency, the number of the Indonesian labor force was recorded at 144.01 million people in February 2022. Supported by a large number of potential human resources, an organization or company can certainly operate effectively and efficiently supported by the role of employees. Employees who work also have the right to Occupational Safety and Health which in its implementation is based on legislation. However, in reality, the number of work accidents in Indonesia is still relatively high and tends to increase. This research aims to find out how influential occupational safety and health are on employee performance for the company. The research method this time is a qualitative research method presented in the form of a narrative literature review. It was found that good employee performance in a company can have a positive impact on the company as a whole. The safety and protection factor at work is one of the keys to improving employee performance. So that the company makes various efforts in realizing protection for employees, one of which is through the provision of Occupational Safety and Health. Kata Kunci: Employee performance, Occupational health, and saf